Soil organic carbon, pH, and ammonium nitrogen controlled changes in bacterial community structure and functional groups after forest conversion - Cao, Xiaoqing; Xia, Kai; Zhao, Hongfei; Deng, Pengfei; Teng, Zhen; Xu, Xiaoniu (Frontiers in Forests and Global Change, 2024)
Introduction Land-use changes significantly impact soil properties in forests, which is an area of concern. Therefore, the effects of changing forest types on soil microbial communities and their functions in northern subtropical forest regions need to be further researched. Methods We used 16S rDNA sequencing and Functional Annotation of Prokaryotic Taxa (FAPROTAX) to assess the variation of soil bacterial communities and potential functions related to carbon (C) and nitrogen (N) cycling in two soil layers (0–10 and 10–30 cm) after the conversion of the secondary masson pine (Pinus massoniana, PM) forest to plantations of slash pine (Pinus elliottii, PE) and Chinese fir (Cunninghamia lanceolata, CL) located in Jingde County, Anhui Province, China. Results The study found that converting coniferous secondary forests to coniferous plantations resulted in a notable increase in soil pH and a decrease in nitrate nitrogen and organic carbon contents. Additionally, soil microbial diversity increased significantly, and microbial community structure changed, particularly in the topsoil. These changes might affect the C- and N-cycling mediated by soil bacteria. The analysis revealed a significant decrease in the abundance of functional groups associated with C-cycling and a significant increase in the abundance of functional groups associated with N-cycling, particularly those associated with denitrification. Soil organic carbon, pH, and ammonium nitrogen were the most critical variables affecting changes in the soil microbial community. Discussion These findings provide valuable information for ecological restoration and future sustainable forest management.